1975
DOI: 10.1083/jcb.65.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Concanavalin A receptors, immunoglobulins, and theta antigen of the lymphocyte surface. Interactions with concanavalin A and with Cytoplasmic structures.

Abstract: The effect of concanavalin A (Con A) on the capping of mouse lymphocyte surface immunoglobulin (surface lg), cross-linked by rabbit anti-mouse Ig antibody, and on the capping of mouse thymocyte 0 antigen, cross-linked by anti-0 alloantibody and rabbit anti-mouse lg antibody, has been studied by immunofluorescence, using fluorescein conjugated Con A and rhodamine-conjugated anti-mouse lg antibody, and by electron microscopy, using native or fluorescein-conjugated Con A and ferritin-conjugated anti-mouse lg anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
52
2

Year Published

1976
1976
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(67 citation statements)
references
References 42 publications
13
52
2
Order By: Relevance
“…In whole lymphocytes, micro filaments are found preferentially underlying the cell surface membrane [4,20] and in surface protrusions such as microvilli [20]. Electron micrographs of the purified plasma membrane vesicles revealed membrane-adherent filamentous material similar in appearance to microfilaments ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In whole lymphocytes, micro filaments are found preferentially underlying the cell surface membrane [4,20] and in surface protrusions such as microvilli [20]. Electron micrographs of the purified plasma membrane vesicles revealed membrane-adherent filamentous material similar in appearance to microfilaments ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been proposed [4,20] that cytoplasmic microfilaments play a key role in the regulation of lymphocyte cell surface receptor mobility. Our results indicate that a protein having a high degree of homology with muscle actin is a major constituent of highly purified preparations of human and pig lymphocyte plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lymphocytes, the translational movement of cell surface-associated immunoglobulin can be demonstrated directly by the patch and cap formation that occurs after treatment with a divalent antibody (3). It has been suggested that, in both lymphocytes and fibroblasts in suspension, the mobility of some macromolecular components of the membrane is subject to transmembrane control by cellular organelles including microfilaments and microtubules (2,4,5).…”
mentioning
confidence: 99%
“…By contrast, the width profiles of cells treated with noninhibitory agents would mimic the width profiles of untreated cells incubated at permissive temperatures. To test this hypothesis the following drugs were used: (1) sodium azide, an inhibitor of capping but not patching (19, ZO), (2) sodium fluoride, which does not interfere with capping (19, ZO), (3) propranolol, a drug that inhibits capping (9, lo), and (4) vinblastine, colchicine, and demecolcine, which reportedly inhibit endocytosis, but not capping (11,19,201. As predicted, cells treated with either azide or propranolol displayed relatively small decreases in their width profiles, and the change in width values was confined to the first 300 sec of the analyses.…”
Section: Other Pharmacological Agentsmentioning
confidence: 99%